The Effect Of Discipline, Stress, And Motivation On Employee Performance At The Housing, Settlement And Land Office Of Buleleng Regency - Gautama, Anak Agung Ngurah Restu; Ardyana, Luh Winda (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The quality of service at the Housing, Settlement Area, and Land Office of Buleleng Regency is highly dependent on the performance of existing employees. Therefore, efforts to improve employee performance should be a major concern. This study aims to determine the influence of discipline, stress, and motivation on employee performance. The research method used is quantitative research with a causal approach. The research sample used the purposive sampling method, so that a sample of 69 respondents was obtained. The results of the study show that discipline has a positive and significant effect on employee performance, stress has a negative and significant effect on employee performance, and motivation has a positive and significant effect on employee performance.